Islamic Wealth Management: Empowerment of Inherited Assets in Sharia-Based Productive Economic Development - Hadi, Muhammad; Alwahidin; Tonasa , Muh (Al-Ulum, 2024)
This study develops an operational framework that integrates Sharia principles, modern management practices, and socioeconomic impact measurement in the context of empowering inheritance assets, using a qualitative approach with an integration of Islamic financial theory analysis methods and empirical studies. The results of the study indicate that the implementation of an Islamic wealth management-based inheritance management model has succeeded in creating a sustainable asset development system and providing a multiplier effect for improving the welfare of heirs and the surrounding community. The business model developed shows innovation in three aspects: Integration of digital technology in the operational management of inheritance assets, development of a tiered profit-sharing system between heirs and managers, and implementation of a Sharia-based sustainability program. The socioeconomic impact is identified through the creation of more than 200 jobs, the strengthening of the local economy, and the development of community capacity.